2020
DOI: 10.1016/j.comnet.2020.107464
|View full text |Cite
|
Sign up to set email alerts
|

On packet marking and Markov modeling for IP Traceback: A deep probabilistic and stochastic analysis

Abstract: From many years, the methods to defend against Denial of Service attacks have been very attractive from different point of views, although network security is a large and very complex topic. Different techniques have been proposed and so-called packet marking and IP tracing procedures have especially demonstrated a good capacity to face different malicious attacks. While host-based DoS attacks are more easily traced and managed, network-based DoS attacks are a more challenging threat. In this paper, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In their approach, reference [15] employs distinct Markovian models for different applications, which are differentiated by their well-known port numbers. Building upon this concept, reference [16] adopts and extends the modeling strategy introduced by [15] specifically for managing TCP connections.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…In their approach, reference [15] employs distinct Markovian models for different applications, which are differentiated by their well-known port numbers. Building upon this concept, reference [16] adopts and extends the modeling strategy introduced by [15] specifically for managing TCP connections.…”
Section: State Of the Artmentioning
confidence: 99%
“…In their approach, reference [15] employs distinct Markovian models for different applications, which are differentiated by their well-known port numbers. Building upon this concept, reference [16] adopts and extends the modeling strategy introduced by [15] specifically for managing TCP connections. The training phase remains consistent across both studies; researchers estimate separate Markovian models for different applications using corresponding training datasets.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The network security is an important topic object of different studies by scientific community as shown in many papers existing in literature [1]- [3]. Conventionally, complex data encryption methods at the upper layers are used to obtain the secure communication.…”
Section: Introductionmentioning
confidence: 99%